Analyzing the Students’ Interest and Ability in Using Chromebook in English Subject at 7th Grade of SMPN 7 Bukittinggi - Wiliyono Swinandes; Absharini Kardena; Irwandi Irwandi; Syahrul Syahrul (Jurnal Masyarakat Madani Indonesia, 2026)
This study examines the impact of Chromebook integration on students' interest and ability in learning English at SMPN 7 Bukittinggi. The present study employs a qualitative case study approach, focusing on grade VII students from classes VII3, VII4, and VII5, which collectively encompass a total of 10 participants, with five females and five males. The data presented herein were collected through a combination of classroom observations and interviews with students and teachers. The findings indicate that Chromebooks facilitate interactive, collaborative, and personalized learning environments, thereby enhancing student motivation, English proficiency, and digital literacy. These tools facilitate essential functions, including the facilitation of assignment access, the provision of feedback, the promotion of peer collaboration, the cultivation of critical thinking, and the promotion of self-assessment. The efficacy of teacher facilitation is paramount for the optimal utilization of Chromebooks. In essence, the integration of Chromebooks into pedagogy fosters dynamic, student-centered environments conducive to autonomy and the development of higher-order thinking skills, underscoring the necessity for continual assessment to address a range of digital learning requirements